Dampak Pandemi Terhadap Pariwisata Halal Jakarta - Adriana, Nia; Nurwahidin, Nurwahidin; Huda, Nurul (UI Scholars Hub, 2021)
In 2019 Indonesia had receiced an award with Malaysia as the best halal tourism destination in the world mastercard-cressent version. There are 10 provinces in Indonesia as priority as halal tourim region in Indonesia, one of them in Jakarta. Jakarta is the main entrance for international and domestic tourist. The Covid 19 virus pandemic in 2020 made the significant impact due this covid, one of sector has the get impact is Tourism sector. Jakarta has the highest number of positive cases (25% from total cases in Indonesi). It estimated that Covid will still happened the until 2021. This study has the purposes to find the impact of the Covid pandemic on halal tourism in Jakarta. The study use kualitatif descriptive method for analysis the information. The source of data used primary and secondary. Beside surveyed the field, the primary data got from interviewed 7 respondens who represent regulators, practitioners, halal tourism experts, academics and community representatives. The result of study are strategies and policies recomendations to face Covid problem and the recomendation which can help halal tourism industry survive during pandemic. Keywords: Jakarta Halal Tourism, Covid-19 Pandemic, Halal Tourism